From consultants to integrators: the evolution and transformation of a consulting business model into technology enterprises in the HR technology market - Irina V. Gladysheva; Alexey O. Gorlov (RUDN Journal of Economics)
The development of technology opens up many opportunities for creating e-business, digital platforms and entrepreneurship. However, the evolution of economic and business processes creates unique platforms and ecosystems, and forces companies to quickly meet the demands of a changing economic environment. In such conditions, consulting becomes a key tool for business and helps to ensure a quick response of the company in challenging times. This study aims at studying business consulting from several points of view: historical development, the present and the future forms, the implementation of new solutions to mitigate current and strategic business risks. The authors of the study attempt to establish the patterns of formation and development of consulting business, to determine the behavior of consulting actors at the national and international levels, to evaluate the key elements of the consulting business model, its reaction to technological changes and success in solving staff-r elated problems. The research was based on facts and statistics of HR and consulting business experts, data on the structure and dynamics of the consulting services market, scientific research by Russian and foreign scientists, and the authors’ own observations. The results of the study may be of interest to specialists in HR technologies, in digitalization and adaptation of business processes, experienced and novice entrepreneurs, management consultants and those who might be interested in the issues discussed.